Studi Analisis Komparatif Antara Ta’wil dan Hermeneutika dalam Penafsiran al-Qur’an - Abdur Razzaq; Deden Mula Saputra (Fakultas Dakwah dan Komunikasi, Universitas Islam Negeri, Raden Fatah Palembang, 2016)
Abstract: Study entitled 'Study of Comparative Analysis Between Ta'wil And Hermeneutics In the interpretation of the Qur'an' provides an overview to the Muslims, that the ta'wil and hermeneutics is something different. Both etymologically,epistemology, historical and applicative methods as interpretations of the al-Qur’an.Ta'wil is the most important part in understanding the Qur'an, while hermeneutics is a tool to interpret and understand the bible. By prioritizing hermeneutics in the interpretation of the al-Qur’an is not able to reach what is revealed by Allah in the Qur'an. Because hermeneutics is not a perfect method applicable if forced to the Qur'an that the original source of Allah SWT, with a language so have a high level of literary taste. Match between ta'wil and hermeneutics is not appropriate, because both come from different sources. And is ultimately resulting in the quality of the interpretation is different.